The Rhetorical Construction of Corporate Logos - Llorente-Barroso, Carmen; García-García, Francisco (Arte, Individuo y Sociedad, 2015)
This research is set in the context of today’s societies, in which the corporate visual symbology of a business, corporation or institution constitutes an essential way to transmit its corporate image. Traditional discursive procedures can be discovered in the development of these signs. The rhetorical strategies developed by the great classical authors appear in the logo-symbols expressing the corporate values of today’s companies. Thus, rhetoric is emerging once again in the sense it had many centuries ago: A repertory of rules that, paradoxically, standardizes the deviations of language and whose control is synonymous with power. The main objective of this study is to substantiate the rhetorical construction of logos using as a model of analysis the classical process of creating discourse. This involves understanding logos as persuasive discourses addressed to a modern audience. Our findings show that the rhetorical paradigm can be considered as a creative model for the construction of an original logo consistent with a company’s image.